Pemulihan Deteriorasi Benih Kedelai (Glycine Max L.) dengan Aplikasi Giberelin - Ratna Dewi; Hery Sutrisno; Nazirwan Nazirwan (Jurnal Penelitian Pertanian Terapan, 2013)
The purpose of this study to determine the role of gibberellins in enhancing the quality of soybean seeds that have experienced deterioration / decline. This research is using a complete randomized group design (RKTL) two factors. The first factor is pengusangan soaking seeds with 20% ethanol. P0 = Without soaking, P1 = Immersion 15 minutes. P2 = Immersion 30 minutes. The second factor is the provision of gibberellins with gibberellin soaking treatment for 2 hours. G0 = without soaking gibberellins, gibberellin soaking G1 = 20 ppm. Each treatment was repeated 3 times. Analysis of data using analysis of variance and to know the difference between treatments, conducted LSD (Least Significant Difference). Each with a real level of 5%. The results are: 1). Application gibberellins showed no recovery of seed deterioration, because pengusangan seeds with ethanol has not shown any significant effect on seed deterioration. 2). Application giberelin the percentage of seed germination and seed vigor percentage lower that 66, 62% and 44.00% compared with that without the application of gibberellins 91.22% and 66.67%, due to the application of gibberellins, sprouts many broke. Might be due to cell division and enlargement of the seed is not offset by the formation of cell walls, so that the cell wall is weak and vulnerable to fractures sprouts 3). Application gibberellins produce a longer hypocotyl length 10.69 cm compared to that without the application of gibberellins that is 7.94 cm. 4). Application gibberellins produce root length is shorter on the 7.73 cm compared to 8.10 cm without the application of gibberellins Keywords: Deterioration, Soybean, Gibberellin